2021
DOI: 10.9734/sajsse/2021/v9i230238
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and Effectiveness of ICT as Agricultural Information Delivery System in Thakurgao, Bangladesh

Abstract: The study was conducted in Thakurgaon sadar Upazila to determine farmers’ perception of the extent and factors of ICTs effectiveness in transferring farming information. A total of 250 people who were already been taken services from different ICT center was selected as sample respondents following a random sampling technique. Primary data were collected using a predesigned interview schedule. Findings revealed that 57.2% of the respondents contacted with Union Digital Center while 38.8% contacted with governm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Participatory approaches, such as farmer field schools, demonstration farms, and peer-to-peer learning networks, can empower farmers to acquire practical skills, share experiences, and adopt context-specific solutions [27,28]. Furthermore, leveraging digital technologies, such as mobile apps, remote sensing, and precision agriculture tools, can enhance the effectiveness and scalability of extension services, reaching a wider audience and addressing specific needs [29][30][31][32].…”
Section: Challenges In Gaps Adoptionmentioning
confidence: 99%
“…Participatory approaches, such as farmer field schools, demonstration farms, and peer-to-peer learning networks, can empower farmers to acquire practical skills, share experiences, and adopt context-specific solutions [27,28]. Furthermore, leveraging digital technologies, such as mobile apps, remote sensing, and precision agriculture tools, can enhance the effectiveness and scalability of extension services, reaching a wider audience and addressing specific needs [29][30][31][32].…”
Section: Challenges In Gaps Adoptionmentioning
confidence: 99%
“…Consumers' perception towards safety of vegetables in the market was measured using a summated rating (Likert type) scale [26,27]. The scale was prepared with larger number of items initially and subjecting them to editing and screening in the light of pre-testing so as to include only the relevant items reflecting both positive and negative effect on a five-point continuum.…”
Section: Measurement Of Variablesmentioning
confidence: 99%
“…Descriptive statistical measures such as range, mean, number and percentage distribution, and standard deviation were used to describe and interpret the data. Chi-square (χ √ ) test was employed to assess the association among the responses of respondents on different perception-related opinions [27]. If the computed value was equal to or greater than the table value of coefficient at a designated level of significance for the relevant degree of freedom, the null hypothesis was rejected and it was concluded that there was a significant relationship between the concerned variables.…”
Section: Compilation and Analysis Of Datamentioning
confidence: 99%
“…As such, any mass-scaled ICT approach that is not properly implemented could conceivably exacerbate the very gender inequalities it seeks to mitigate. For instance, ICT-based educational extension services that focus on increasing agricultural training in the general population could successfully lead to better attended events [27][28][29], but if these larger events are dominated by male attendance, women may be reluctant to participate, especially in traditional male-dominated environments, such as those commonly associated with agriculture.…”
Section: Introductionmentioning
confidence: 99%